2014
DOI: 10.3109/14659891.2014.911977
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of anabolic steroid use amongst gym users in the United Kingdom: motives, beliefs and experiences

Abstract: The illicit use of anabolic steroids amongst the gym population continues to rise in the United Kingdom presenting serious challenges to public health. This study used qualitative interviews to explore the experiences of 24 users of anabolic steroids and investigate their motives and experiences. Body satisfaction was a motivating factor in the use of anabolic steroids. Anabolic steroid users' drug use and associated behaviour were influenced by numerous sources of information, in particular, first-hand accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 19 publications
(22 reference statements)
5
78
0
5
Order By: Relevance
“…Significantly in this respect, this study found that whereas all steroid users had obtained sterile needles and syringes from services only about half of them, predominantly those gaining access to steroid clinics, reported seeking additional information from these programmes with few reporting that they sought information about how to use anabolic steroids in the least harmful way. Here, the availability of knowledge within groups of steroid users seemed to act as a barrier to information from health authorities, which resonates with previous findings that health services are not usually seen as credible sources of information 7 14 16 22. Services must identify more appropriate ways of providing credible information that will be valued and result in positive behaviour change.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Significantly in this respect, this study found that whereas all steroid users had obtained sterile needles and syringes from services only about half of them, predominantly those gaining access to steroid clinics, reported seeking additional information from these programmes with few reporting that they sought information about how to use anabolic steroids in the least harmful way. Here, the availability of knowledge within groups of steroid users seemed to act as a barrier to information from health authorities, which resonates with previous findings that health services are not usually seen as credible sources of information 7 14 16 22. Services must identify more appropriate ways of providing credible information that will be valued and result in positive behaviour change.…”
Section: Discussionsupporting
confidence: 80%
“…Empirical qualitative studies show that users exchange anabolic steroid-related information on methods to reduce or avoid adverse effects 14. As a consequence, many users ignore or perceive the risk of steroid usage as relatively minor 7 15–17. Steroid users who seek the support of peer users but avoid social censure by keeping their use of drugs a secret from others may also serve as a mechanism that promotes harm 18.…”
Section: Introductionmentioning
confidence: 99%
“…The immediate social networks of respondents such as intimate partners, relatives, as well as friends or teammates also emerged as important sources of AAS [6,11,21,23-25,28,32,38,39,42,46,49] during the initiation of AAS use.…”
Section: Resultsmentioning
confidence: 99%
“…Of particular significance is the injecting use of IPED from which a new and unique group of injecting drug users has emerged. IPED injector engagement with needle exchange services (Kimergard 2015) has mainstreamed the provision of such services which were traditionally confined to injecting psychoactive drug user groups. IPED users typically disassociate from an injecting drug user identity as use is perceived as socially acceptable bodywork, motivated through pursuit of health and appearance ideals.…”
Section: Introductionmentioning
confidence: 99%